2005
DOI: 10.2514/1.15095
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cavity-Stabilized Flames in a Supersonic Flow

Abstract: NOTES are short manuscripts describing new developments or important results of a preliminary nature. These Notes should not exceed 2500 words (where a figure or table counts as 200 words). Following informal review by the Editors, they may be published within a few months of the date of receipt. Style requirements are the same as for regular contributions (see inside back cover).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…Previous research has shown that in the case of a cavity with the fuel injector inside the cavity, the open cavity with the aft ramp has a higher performance as a flame holder [22], although the performance depends on injection position [22,30]. However, in the case of a cavity with upstream fuel injection, a small L/D has better performance for flame stabilization compared to the cavity with the aft ramp.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous research has shown that in the case of a cavity with the fuel injector inside the cavity, the open cavity with the aft ramp has a higher performance as a flame holder [22], although the performance depends on injection position [22,30]. However, in the case of a cavity with upstream fuel injection, a small L/D has better performance for flame stabilization compared to the cavity with the aft ramp.…”
Section: Introductionmentioning
confidence: 78%
“…A cavity model also enhances the characteristics of air mixing [20], and it has been investigated as a flame holding mechanism for the scramjet engine [21][22][23][24][25][26][27][28][29][30][31][32]. Additionally, the cavity model possesses the feature of comparatively low profile drag compared to a step injector model [33,34] or strut injector model [35,36], although this feature depends strongly on the cavity geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies [6][7][8][9][10] have shown that a well-designed cavity is able to provide a recirculation zone in which the hot gas will act as a heat source and a radical pool to stabilize the combustion process in supersonic flow. The mechanism of flame stabilization in supersonic flows is very complicated due to the strong interaction between the chemical reaction and the turbulent flow in the combustor.…”
Section: Introductionmentioning
confidence: 99%
“…Schlieren photography has been widely employed to visualize the processes of fuel injection, [1][2][3][4][5] fuel-air mixing, [6][7][8] fuel ignition, 9,10 flame holding, [11][12][13] shock/boundary interaction, [14][15][16][17] etc. However, few literatures could be found for the visualization of the combustion process in a scramjet combustor.…”
Section: Introductionmentioning
confidence: 99%